Cross-script L2-L1 noncognate translation priming in lexical decision depends on L2 proficiency: Evidence from Japanese–English bilinguals*. Issue 5 (31st July 2015) - NAKAYAMA, MARIKO; IDA, KEISUKE; LUPKER, STEPHEN J.
Abstract : Previous research with unbalanced, different-script bilinguals has typically produced null L2-L1 noncognate masked translation priming effects in lexical decision tasks (LDT). Two novel models of the bilingual mental lexicon have emerged to account for these null results: the episodic L2 hypothesis and the Sense model. In contrast, the BIA+ model predicts significant priming whenever bilinguals are sufficiently proficient in L2. Using Japanese–English bilinguals, the role of L2 proficiency in L2-L1 noncognate translation priming in an LDT was examined. In Experiments 1 and 2, significant priming effects were observed for highly proficient bilinguals. In contrast, in Experiment 3, less-proficient bilinguals produced a null priming effect. This pattern demonstrates that L2-L1 priming effects do arise in an LDT and those effects are modulated by L2 proficiency, consistent with the BIA+ model's expectations. The pattern can be also explained by the episodic L2 hypothesis, provided that certain modifications are made to its assumptions.